Production performance, egg quality, and economic profitability of Isa Brown hens that received Eucalyptus globulus leaf powder-based diet (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: The Eucalyptus globulus leaf powder (EgP) was used in this study to evaluate its effects on the productive performance, physical quality of eggs, and profitability of Isa Brown laying hens. Materials and Methods: A total of 400 20-week-old Isa Brown laying hens were randomly allocated into 5 groups of 4 replicates each, with 20 hens per pen for 24 weeks. The groups comprised 0% EgP without AGP (negative control, group T-); 0% EgP with the use of AGP (positive control, group T+); 0.25% EgP without AGP (group T1); 0.5% EgP without AGP (group T2); and 1% EgP without AGP (group T3). Results: The study revealed that the average laying rate was higher in T2 hens with a higher average egg weight, similar to T3. The feed conversion ratio was statistically lower in the EgP and AGP groups than in the negative control group. With storage duration, the eggshell weight was higher, and the Haugh unit significantly decreased less than that of hens treated with EgP compared to the control groups. The gross operating income was positive only for T2 and T3 hens during the 30th to 44th week (phase 2 of laying), and in this phase, the use of E. globulus leaf at 0.5% realized a margin of 10.63 F CFA on the production of an egg compared to the antibiotic group. Conclusion: The inclusion of 0.5% EgP in the diet of hens resulted in the highest level of profitability and egg quality observed throughout the 24-week production period.J. Adv. Vet. Anim. Res., 12(4): 1217–1227, December 2025http://doi.org/10.5455/javar.2025.l982